GuideBot. A Tour Guide System Based on Mobile Robots. (6th November 2013) - López, Joaquín; Pérez, Diego; Santos, María; Cacho, Miguel
There is a growing interest in the use of tour guide mobile robots in different environments such as museums, exhibitions and fairs. This type of robot should have autonomy, robust perception and navigation systems, and should also be oriented towards close interaction with humans. In this paper we present an automatic tour guide system based on a set of mobile platforms that interact with visitors to help them in different tasks. These tasks include giving tours to visitors, helping them find points of interest in a building and providing information about elements in the stands in a fair. Over the last few years, many tour guide robots have been developed and used in museums and at events. Most of these systems are based on a single robot and they do not include mechanisms to exchange information with the building automation system. The approach presented here uses several robots connected to a central server. The system also includes different devices in the building that are connected through a fieldbus to the central server. The system was developed with the Robotics Integrated Development Environment (RIDE) and was tested intensively at different events.